The Influence Of Health Education About The Danger Of Smoking The Knowledge, Attitudes And Behavior Of Adolescent At Smpn 12 Bekasi In 2025 - Yulia Agustina; Tia Jesica (Jurnal Ners, 2026)
Background: Health education is a crucial effort to curb smoking by increasing adolescents' understanding and awareness of the harmful effects of smoking. Through appropriate counseling, it is hoped that adolescents will develop positive attitudes and healthy lifestyles, thereby creating a smoking-free young generation. Cigarettes are a leading cause of premature death, which is preventable. Various studies have proven that the toxic substances in cigarettes are extremely harmful to health. To date, smoking remains a serious problem in Indonesia. Although some people are aware of the negative health impacts of smoking, many still choose to smoke. Adolescents aged 13–19 are among the most vulnerable groups because they are at a developmental stage with various complex issues. Health education plays a crucial role in raising awareness and expanding public knowledge about ways to maintain and improve health, both for themselves, their families, and their surroundings. Research Objective: To determine the effect of health education about the dangers of smoking on the knowledge, attitudes, and behavior of adolescents at SMPN 12 Bekasi City. Research Method: This research is a quantitative, descriptive-analytical study using a quasi-experimental design. This study employed a pre-test and post-test design approach. Intervention: Health education on the dangers of smoking will be provided through lectures using LCD screens and PowerPoint (PPT) presentations. The sampling technique used in this study was random sampling with 125 respondents. Research Results: The knowledge data before and after the study showed a distribution of 0.000 (p-value <0.05), and the attitude data before and after the study showed a distribution of 0.000 (p-value <0.05). The behavior data before and after health education on the dangers of smoking showed a value of α = 0.010 (p-value <0.05), indicating a significant effect between health education on the dangers of smoking on the knowledge, attitudes, and behavior of students at SMPN 12 Bekasi in 2025. Conclusions: There is a significant effect between health education on the dangers of smoking on the knowledge, attitudes, and behavior of students at SMPN 12 Bekasi in 2025. The results of this study are expected to inform the development of a health promotion socialization program aimed at increasing knowledge and preventing the increase in the number of adolescent smokers.